In vitro Anti-oxidant, Antimicrobial, in silico Molecular Docking Analysis, and Phylogenetic Analysis of Anoectochilus elatus - Muthusamy, Sathishkumar; Sellappan, Selvi; Arulselvan, Palanisamy; Alarfaj, Abdullah A (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Medicinal plants have long been valued for their therapeutic properties, offering a rich reservoir of bioactive compounds. Across millennia, diverse cultures worldwide have developed intricate systems of traditional medicine, utilizing plant-based remedies to treat a wide range of ailments. Objectives: This study investigates the in vitro antioxidant and antimicrobial activities, along with in silico analyses, of the roots of Anoectochilus elatus. Materials and Methods: Crude saponins were isolated from the root extracts, and their free radical scavenging and antimicrobial activities were evaluated using standard methods. In silico analyses and phylogenetic investigations were performed to identify key protein constituents associated with the medicinal properties of A. elatus roots, focusing on Ribulose-1,5-bisphosphate carboxylase and Maturase K. Results: Isolated saponins from A. elatus root extracts exhibited significant antioxidant and antimicrobial activities against various pathogens. In silico and phylogenetic analyses highlighted the potential therapeutic roles of Ribulose-1,5-bisphosphate carboxylase and Maturase K proteins in A. elatus. Conclusion: This study demonstrates the antioxidant potential and antimicrobial efficacy of saponins derived from A. elatus roots. Furthermore, in silico findings suggest a crucial role for Ribulose-1,5-bisphosphate carboxylase and Maturase K in mediating the plant’s therapeutic effects.
Keywords: Pathogens; Antioxidant; Anoectochilus elatus; In silico analysis; Maturase K.